A “borracha quântica” aplicada como atividade experimental no ensino da física quântica para alunos do ensino médio - Monteiro Junior, Francisco Miranda (2021)
This work presents an experience report on the application of a didactic sequence for teaching quantum physics to students high school students who have already studied optics, wave and electricity. As a form of support for the teaching sequence, an experimental activity was developed called “quantum rubber”. This teaching sequence was developed with the aim of adding more knowledge regarding the teaching of quantum mechanics, which in itself is difficult to understand and difficult to access. So the intention is to find support to teach something that can illustrate some effects, taking into account the impossibility of something concrete. The support found is based on a teaching sequence that consists of seven stages (classes) where in these stages the knowledge construction process is divided into three actions: 1) The presentation of the problem situation to the student and the objectives that we must achieve; 2) The presentation of the objects that will be part of the assembly of the prototype; 3) The setting up of the experimental activity: the “quantum rubber”. We also used two assessments in order to analyze the students' previous knowledge and the knowledge acquired at the end of the entire teaching and learning process. The results of this work made it possible to improve the didactic sequence developed, which is presented in the Appendix as an educational product to assist high school physics teachers in approaching the concept of quantum mechanics for their students.